Concise Review; The Recent Methods that Enhance the Osteogenic Differentiation of Human Induced Pluripotent Stem Cells - Hou, Yongchun; Yan, Zi; Wu, Zhongqi (Current Stem Cell Research & Therapy, 2021)
Bone regeneration is a critical problem in modern clinical practice. Osteocytes are the most abundant cell population of mature adult bone that play a major role in the regulation of bone formation. In humans, segmental bone defects cannot be repaired by endogenous regenerative mechanisms. Bone tissue engineering (BTE) is a promising option for the treatment of difficult segmental and skeletal defects. BTE requires suitable cell sources with rapid expansion and adequate function, inducible factors, and scaffolds to successfully regenerate or repair the bone injury. To overcome the disadvantages of using allogeneic and autologous tissue grafts, stem cell-based therapy has progressed in regenerative medicine. In the past few decades, numerous attempts have been made to generate osteocytes by using pluripotent stem cells (PSCs) to repair and regenerate bone defects. Human induced pluripotent stem cells (hiPSCs) are PSCs that can self-renew and differentiate into a variety of cell types. Reprogramming of human somatic cells into hiPSCs provides a new opportunity for regenerative medicine, cell-based drug discovery, disease modeling, and toxicity assessment. The ability to differentiate hiPSCs from mesenchymal stem cells (iPSC-MSCs) is essential for treating bone-related damages and injuries. Several in vitro studies revealed that the cell origin of iPSCs, a combination of transcription factors, the type of promoter in the vector, transduction methods, scaffolds, differentiating techniques, and culture medium, may affect the osteogenic differentiation potential of hiPSCs. This review will focus on several factors that influence the osteogenic differentiation of human iPSCs.
Keywords: osteocytes